2013
DOI: 10.37190/epe130412
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of municipal solid waste systems: Cracow case study

Abstract: The evaluation method to compare municipal solid waste management (MSWM) systems has been presented. The results of the integrated waste management model (IWM-1), were used as the input data for the analysis. The results were integrated into life cycle analysis (LCA) impact categories. The authors present possible to calculate categories, and calculate them for the two MSWM scenarios. Next, the system performance was compared using a multicriteria method, called analytic hierarchy process (AHP). The hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
3
0
1
Order By: Relevance
“…The actual composition and quantity of landfill gas can vary significantly in space and time. The main reason why landfill gas is monitored and regulated by legislation and relevant standards is that its main components, methane, and carbon dioxide, are greenhouse gases whose negative effects on the environment are well known; however, methane is much more significant for climate change and therefore its removal from landfill gas is a priority [10,11].…”
Section: Landfill Gas Management In the Czech Republicmentioning
confidence: 99%
“…The actual composition and quantity of landfill gas can vary significantly in space and time. The main reason why landfill gas is monitored and regulated by legislation and relevant standards is that its main components, methane, and carbon dioxide, are greenhouse gases whose negative effects on the environment are well known; however, methane is much more significant for climate change and therefore its removal from landfill gas is a priority [10,11].…”
Section: Landfill Gas Management In the Czech Republicmentioning
confidence: 99%
“…It was shown that a good relation between the industrial preventive environmental protection strategies and substantial savings exists. It was also shown that the efficient management of industrial waste improves the competitiveness if handles the waste properly (Stypka & Flaga-Maryanczyk, 2013).…”
Section: Cost-benefit Analysis (Cba)mentioning
confidence: 99%
“…A more detailed analysis of the obtained results allow to draw conclusion about how much the environmental performance of system B is increased by substituting the landfilling with the incineration and extension of the waste collection system. Also, the local and global environmental impacts can be distinguished [3].…”
Section: Multicriteria Analysis Of the Cracow Msw Systemsmentioning
confidence: 99%